2021
DOI: 10.12775/jehs.2021.11.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine – assesment of society’s opinion

Abstract: During the COVID-19 pandemic, it is necessary to use some safety measures due to decrease spreading of the virus. One of them is introducing teleconsultations as a form of medical consultation. It allows patients to talk with the doctor without visiting the hospital. The aim of the study is to present the society's opinion on teleconsultations and its most common disadvantages. The method of the study was an online survey, conducted on 68 people, whose answers were statistically analyzed. During the pandemic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The benefits resulting from the current situation are also indicated by Teleon and Włoszczak-Szybzda, who claim that the pandemic forces the use of new media in medical practice and contributes to their more frequent use; thus, it is supposed to reduce technophobia in the medical community and increase patients' access to basic medical specialists [11]. It is worth noting that the study by Zawiślak et al showed that the majority of respondents (73%) would like to be able to receive telephone advice also after the end of the pandemic [12].…”
Section: Discussionmentioning
confidence: 99%
“…The benefits resulting from the current situation are also indicated by Teleon and Włoszczak-Szybzda, who claim that the pandemic forces the use of new media in medical practice and contributes to their more frequent use; thus, it is supposed to reduce technophobia in the medical community and increase patients' access to basic medical specialists [11]. It is worth noting that the study by Zawiślak et al showed that the majority of respondents (73%) would like to be able to receive telephone advice also after the end of the pandemic [12].…”
Section: Discussionmentioning
confidence: 99%